The Ideal City - Federico M. Butera (Agathón)
The planetary boundaries transgressions show that the functional integrity of the biosphere is in great danger. The cause lies in human activities, which are the product of the current economic and cultural model. The complex environmental system, with its tight interconnections between various planetary boundaries, is closely linked to another complex system: human society. Together, they form a super-system whose stability is at risk. The most significant cause of this instability is represented by urban centres, due to their metabolism, the analysis of which allows us to identify actions to minimise their environmental and social impacts. To implement these actions, since urban centres are also complex systems, we must abandon the planning models followed so far and adopt one more suitable for them.